Silicon-based composite material with blood vessel promoting and antibacterial activity as well as preparation method and application of silicon-based composite material

By performing in-situ deposition reaction on porous silicon-based nanomaterials, Pt-PSi silicon-based composite materials with provascularization and antibacterial activities were prepared, which solved the problem of insufficient application of existing nanoenzymes in burn-infected wounds and achieved efficient wound healing and antibacterial effects.

CN119733079APending Publication Date: 2025-04-01HANGZHOU NORMAL UNIVERSITY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411952986.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The application of existing nanoenzymes in burn-infected wounds has complex synthetic steps, low or unstable activity, and lack of ability to promote angiogenesis, which limits its functional application in the coordinated treatment of burn-infected wounds.

Method used

Porous silicon (PSi)-based nanomaterials were used to carry out in-situ deposition reactions with platinum (Pt) precursors under citric acid medium to prepare Pt-PSi silicon-based composite materials with good dispersion, uniformity and high density Pt distribution. This material achieves uniform nucleation and efficient loading of Pt through citric acid regulation, and has provascular and antibacterial activities.

Benefits of technology

The good dispersion and catalytic activity of Pt-PSi silicon-based composite materials are achieved, and the excellent near-infrared photothermal conversion ability and peroxidase-like catalytic activity is achieved, which significantly improves the healing efficiency of burn-infected wounds and reduces the use of antibiotics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005215278870000011
    Figure HDA0005215278870000011
  • Figure HDA0005215278870000012
    Figure HDA0005215278870000012
  • Figure HDA0005215278870000021
    Figure HDA0005215278870000021
Patent Text Reader

Abstract

The invention provides a preparation method of a silicon-based composite material with blood vessel promoting and antibacterial activity. Compared with the prior art, a proper amount of citric acid is added in the in-situ deposition reaction process, in the reaction process, a Pt precursor obtains electrons from surface hydrides of porous silicon nano-particles and is reduced into a metal Pt substance, the acidity of a precursor solution can be improved by adding citric acid, hydrolysis of precious metal salt is inhibited, and meanwhile, the metal Pt material is prepared. A carboxyl functional group on the surface of citric acid can effectively adsorb metal cations, so that the obtained silicon-based composite material has good dispersity, uniform and high-density Pt distribution and good nano-enzyme and photo-thermal activity, and is finally successfully used for blood vessel promotion and antibacterial treatment of infected burn wounds; moreover, the synthesis process of the material is simple, convenient and mild, and is completely carried out in a water phase, so that the potential toxicity of adding other surfactants or the expensive property of professional equipment for electrochemical deposition can be avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biomedicine technology, and in particular relates to a silicon-based composite material with angiogenic and antibacterial activities, and a preparation method and application thereof. Background Art

[0002] Burns, usually caused by high temperature, flame, electric current and chemicals, are one of the most devastating traumas. Clinically, burn wound healing is often hampered by impaired regeneration of deep dermal tissue and persistent infection, which may even lead to sepsis. Burn-infected wounds pose a serious threat to the life and health of patients. According to the World Health Organization (WHO), more than 11 million people suffer from burns every year worldwide, with a high mortality rate, estimated to be more than 250,000 deaths per year. Compared with normal wounds, the microenvironment of burn wounds has a series of complex characteristics, such as overexpression of reactive oxygen species (ROS), long-term inflammation, increased risk of bacterial infection, and insufficient vascularization, which will further restrict the healing process. Although traditional drug treatments such as antibiotics can treat burn-infected wounds to a certain extent, the single therapeutic function of antibiotics cannot meet the clinical needs of multiple treatments for burn-infected wounds in terms of clearing ROS, regulating inflammation, and promoting angiogenesis to accelerate wound healing. In addition, excessive use of antibiotics may lead to increased bacterial resistance, thus affecting the therapeutic effect. Therefore, it is urgent to design and develop efficient and safe biological agents with multiple therapeutic functions to accelerate the healing process of burn-infected wounds from multiple angles.

[0003] In recent years, the continuous breakthroughs and progress of nanomaterials in the field of biomedicine have provided opportunities for the development of efficient antibiotic-free treatments that can effectively prevent infection and promote the healing of burn infected wounds. Many nanomaterials have also been shown to have biomimetic enzyme activity, which are also called nanozymes. Nanozymes can solve many challenges associated with natural enzymes, such as potential antigenicity, poor bioavailability, and low stability under pathological conditions, showing great potential as a substitute for natural enzymes in wound treatment applications. At present, the therapeutic effect of nanozymes in burn wounds is mainly manifested in regulating the ROS level of the inflammatory microenvironment and effective bactericidal ability, such as the Chinese patents with publication numbers CN116019928A and CN114053473A. In addition, nanozymes can also be further combined with other therapies (such as photothermal therapy, photodynamic therapy, magnetic hyperthermia, etc.) to activate and amplify specific therapeutic effects. It has become a research hotspot in the field of wound treatment, such as the Chinese patents with publication numbers CN118286487A and CN115501339A.

[0004] Although nanozymes have been widely used to regulate ROS and fight bacteria, their synthesis steps are complex and their activity is low or unstable in physiological environments. In addition, poor vascularization of burn wounds can severely limit the delivery of oxygen and nutrients to the wound site, complicating the healing process and prolonging the healing time. Currently, few nanozymes have the ability to promote angiogenesis, which greatly limits the functional application of nanozymes in the synergistic treatment of burn infected wounds.

[0005] Porous silicon (PSi) materials have been widely used as carriers or medical treatment materials in the field of biomedicine due to their advantages such as simple preparation process, high specific surface area, adjustable pore structure, easy surface modification, good biocompatibility and degradability. The Chinese patent with publication number CN112142054A discloses that the only degradation product of PSi under physiological conditions, silicon ions, has high biosafety, can stabilize the expression of vascular growth factor (VEGF) and hypoxia-inducible factor (HIF-1a), promote the migration and vascularization of skin cells, and is an effective pro-angiogenic biomaterial. Therefore, PSi-based nanomaterials have great potential in the treatment of angiogenesis in various diseases, including chronic wounds. However, the antibacterial effect of PSi is limited, which limits its effectiveness in treating burn infection wounds. In order to meet this challenge, using the rich pore structure of PSi to load nanozymes with efficient antibacterial activity is expected to become a promising strategy. Therefore, it is imperative to rationally design and construct functionalized PSi-based nanozymes with multiple stimulus responses to treat burn infected wounds in a more precise and effective manner by combining antibacterial, anti-inflammatory, and pro-angiogenic activities.

[0006] In recent years, Pt-based nanoparticles have attracted much attention in the fields of antibacterial, antioxidant and wound treatment due to their excellent nanozyme mimetic properties, photothermal activity, in vivo stability, simple and controllable synthesis and excellent biosafety. However, Pt-based nanoparticles have large particle size, uneven distribution and unclear catalytic mechanism, resulting in low atomic utilization, limited catalytic activity and application. Summary of the invention

[0007] In view of this, the technical problem to be solved by the present invention is to provide a silicon-based composite material with pro-angiogenic and antibacterial activity, and a preparation method and application thereof. The silicon-based composite material is a Pt-PSi hybrid material with good dispersibility, uniform and high-density Pt distribution, and exhibits good nanozyme and photothermal activity.

[0008] The present invention provides a method for preparing a silicon-based composite material having angiogenic and antibacterial activities, comprising the following steps:

[0009] S1) providing porous silicon nanoparticles;

[0010] S2) The porous silicon nanoparticles and citric acid are mixed and heated in water, and then a platinum precursor is added to react to obtain a silicon-based composite material.

[0011] Preferably, in step S2), the pH value of the system is adjusted to 4-7 after mixing.

[0012] Preferably, the platinum precursor is selected from one or more of chloroplatinic acid, platinum chloride and platinum acetate.

[0013] Preferably, the reaction temperature in step S2) is 50°C to 70°C; and the reaction time is 1 to 3 hours.

[0014] Preferably, the step S2) is specifically:

[0015] The porous silicon nanoparticles are mixed with water, and then a citric acid aqueous solution is added, heated, and then a platinum precursor solution is added to react to obtain a silicon-based composite material.

[0016] Preferably, the concentration of the citric acid aqueous solution is 1 to 2000 mg / mL;

[0017] The concentration of the platinum precursor solution is 1 to 200 mmol / L;

[0018] The ratio of the porous silicon nanoparticles to water is 1 g: (1-5) mL.

[0019] Preferably, the porous silicon nanoparticles are prepared according to the following method:

[0020] A1) using a P-type boron-doped silicon wafer as an anode and a mixed solution of ethanol and a 40-50 wt % hydrofluoric acid aqueous solution as an electrolyte, performing constant current electrolysis to obtain a porous silicon layer;

[0021] A2) using the porous silicon layer as an anode and a 3-5 wt % hydrofluoric acid aqueous solution as an etching electrolyte to perform constant current etching to obtain a porous silicon film;

[0022] A3) The porous silicon film is subjected to ultrasonic treatment to obtain porous silicon nanoparticles.

[0023] The present invention also provides a silicon-based composite material with angiogenic and antibacterial activity prepared by the above preparation method, comprising porous silicon nanoparticles and nanoplatinum particles loaded on the porous silicon nanoparticles; the porous silicon nanoparticles have vertical channels.

[0024] The present invention also provides an application of the silicon-based composite material with angiogenic and antibacterial activities prepared by the above preparation method in the preparation of angiogenic materials.

[0025] The present invention also provides an application of the silicon-based composite material with angiogenic and antibacterial activity prepared by the above preparation method in the preparation of wound dressings.

[0026] The present invention provides a method for preparing a silicon-based composite material with angiogenic and antibacterial activities, comprising the following steps: S1) providing porous silicon nanoparticles; S2) mixing the porous silicon nanoparticles with citric acid in water and heating them, and then adding a platinum precursor to react to obtain the silicon-based composite material. Compared with the prior art, the present invention solves the problem that the reaction kinetics of Pt deposition is poor and it is difficult to directly use the direct reaction of PSi and Pt precursor to obtain a nanocomposite with good nucleation and uniform dispersion in actual operation by adding an appropriate amount of citric acid during the in-situ deposition reaction, which is beneficial to the performance and batch production of the nanocomposite. During the reaction, the Pt precursor obtains electrons from the surface hydride of the porous silicon nanoparticles and is reduced to a metal Pt substance. The addition of citric acid can increase the acidity of the precursor solution and inhibit the hydrolysis of the noble metal salt. At the same time, the carboxyl functional group on the surface of the citric acid can effectively adsorb metal cations, thereby ensuring the uniform nucleation of Pt on the surface of the porous silicon nanoparticle template during the in-situ reduction process, so that the obtained silicon-based composite material has good dispersibility, uniform and high-density Pt distribution, and exhibits good nanozyme and photothermal activity, and is finally successfully used for angiogenesis and antibacterial treatment of infected burn wounds. Furthermore, the synthesis process of the material is simple, convenient, mild, and is completely carried out in the aqueous phase, which can avoid the potential toxicity of adding other surfactants or the expensiveness of professional equipment for electrochemical deposition. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a transmission electron microscopy image of the PSi nanoparticles obtained in Example 1 of the present invention;

[0028] Figure 2 TEM images of the Pt-PSi silicon-based composite materials obtained in Example 1 and Comparative Examples 1 to 5 of the present invention;

[0029] Figure 3 1W / cm at 808nm 2 Photothermal curves of water, PSi material, and Pt-PSi composite material under NIR light irradiation and photothermal stability test results of the Pt-Psi silicon-based composite material obtained in Example 1;

[0030] Figure 4 The results of nanozyme activity tests on different materials are shown in Figure 2.

[0031] Figure 5 This is a diagram showing the release of silicon ions from different materials during material degradation and dissolution in a buffer solution that simulates the wound microenvironment.

[0032] Figure 6 This is a comparison chart of the antibacterial effects of different groups;

[0033] Figure 7 This is the cell viability test result diagram corresponding to the Pt-PSi material under NIR laser irradiation and without;

[0034] Figure 8 The results of the treatments in different groups on the migration ability of endothelial cells are shown in the figure;

[0035] Fig. 9 This is a photo of an in vivo vascular experiment;

[0036] Fig.10 These are images of wound size and quantitative analysis results of wound size at different time points after treatment in different groups. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0038] The present invention provides a method for preparing a silicon-based composite material with angiogenic and antibacterial activities, comprising the following steps: S1) providing porous silicon nanoparticles; S2) mixing the porous silicon nanoparticles with citric acid in water and heating them, and then adding a platinum precursor to react to obtain the silicon-based composite material.

[0039] The present invention adopts the citric acid adjustment method for the first time and introduces uniformly dispersed and dense Pt spherical nanoparticles with small size into the porous silicon nanoparticles based on the in-situ deposition reaction of the noble metal precursor and the porous silicon nanoparticles. The synthesis process of the material is simple, convenient, mild, and is completely carried out in the water phase, which can avoid the potential toxicity of adding other surfactants.

[0040] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.

[0041] In the present invention, the porous silicon nanoparticles have vertical channels.

[0042] In a specific embodiment provided by the present invention, the porous silicon nanoparticles are preferably prepared according to the following method: A1) using a P-type boron-doped silicon wafer as an anode and a mixed solution of ethanol and a 40-50wt% hydrofluoric acid aqueous solution as an electrolyte, constant current electrolysis is performed to obtain a porous silicon layer; A2) using the porous silicon layer as an anode and a 3-5wt% hydrofluoric acid aqueous solution as an etching electrolyte, constant current etching is performed to obtain a porous silicon film; A3) the porous silicon film is subjected to ultrasonic treatment to obtain porous silicon nanoparticles. The porous silicon nanoparticles provided by the present invention are prepared by a top-down electrochemical etching method, and can be obtained by peeling off the obtained porous silicon layer (PSi layer) and ultrasonic crushing treatment.

[0043] In the present invention, the volume ratio of ethanol to 40-50 wt % hydrofluoric acid aqueous solution in the mixed solution of ethanol and 40-50 wt % hydrofluoric acid aqueous solution in step A1) is preferably 1:(3-5), more preferably 1:4.

[0044] In the present invention, in step A1), a platinum electrode is used as the cathode.

[0045] In the present invention, the current density of the constant current electrolysis in step A1) is preferably 70 to 80 mA·cm -1 , more preferably 75 to 80 mA·cm -1 , and preferably 77 mA·cm -1 .

[0046] In the present invention, the time of constant current electrolysis in step A1) is 5 to 15 minutes, more preferably 8 to 12 minutes, and even more preferably 10 minutes.

[0047] In the present invention, the constant current etching in step A2) uses a platinum electrode as a cathode.

[0048] In the present invention, the etching electrolyte in step A2) is preferably a 3-4 wt % hydrofluoric acid aqueous solution, more preferably a 3-3.5 wt % hydrofluoric acid aqueous solution, and even more preferably a 3.3 wt % hydrofluoric acid aqueous solution.

[0049] In the present invention, the current density of the constant current etching in step A2) is preferably 30 to 50 mA·cm -1 , more preferably 30 to 40 mA·cm -1 , and more preferably 30 to 35 mA·cm -1 .

[0050] In the present invention, the constant current etching time in step A2) is preferably 5 to 10 min, more preferably 5 to 8 min, and even more preferably 5 min.

[0051] In the present invention, the power of the ultrasonic treatment in step A3) is preferably 300-800 W, more preferably 400-600 W, more preferably 450-550 W, and most preferably 500 W; the time of the ultrasonic treatment is preferably 1-5 h, more preferably 2-4 h, and more preferably 3 h.

[0052] In the present invention, after the ultrasonic treatment in step A3), the supernatant is preferably centrifuged and washed to obtain porous silicon nanoparticles; the centrifugal speed is preferably 5000-15000 rpm, more preferably 8000-12000 rpm, and more preferably 10000 rpm; the centrifugal time is preferably 5-15 min, more preferably 8-12 min, and more preferably 10 min; the washing is preferably carried out with ethanol; ultrasmall particles can be removed by washing, and porous silicon nanoparticles can be obtained by collecting the bottom product.

[0053] The porous silicon nanoparticles and citric acid are mixed and heated in water, and then a platinum precursor is added to react; after mixing, the pH value of the system is preferably adjusted to 4-7, more preferably 4-6, and more preferably 4-5; in the present invention, the pH value of the system can be adjusted by adding an inorganic acid solution and / or an inorganic alkali solution; the inorganic acid solution can be an inorganic acid solution well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably a hydrochloric acid solution; the concentration of the inorganic acid solution is preferably 0.005-0.05 mol / L, more preferably 0.005-0.03 mol / L, more preferably 0.008-0.02 mol / L, and most preferably 0.01 mol / L; the inorganic alkali solution can be an inorganic alkali solution well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably an alkali metal hydroxide solution, and more preferably a sodium hydroxide solution; the concentration of the inorganic alkali solution is preferably 0.005-0.05 mol / L, and more preferably 0.005-0.03 mol / L. ol / L, more preferably 0.008-0.02 mol / L, most preferably 0.01 mol / L; the platinum precursor can be a platinum precursor known to those skilled in the art without any special restrictions, and in the present invention, it is preferably one or more of chloroplatinic acid, platinum chloride and platinum acetate; the ratio of the porous silicon nanoparticles to the platinum precursor is preferably 1g: (0.00002-0.004) mmol, more preferably 1g: (0.0002-0.004) mmol, and more preferably 1g: (0.0002-0.004) mmol. Preferably, it is 1g: (0.0005-0.003)mmol, more preferably, it is 1g: (0.0008-0.002)mmol, more preferably, it is 1g: (0.0008-0.0015)mmol, and most preferably, it is 1g: 0.001mmol; the reaction temperature is preferably 50°C-70°C, more preferably 55°C-65°C, and most preferably 60°C; the reaction time is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 2h.

[0054] The present invention uses an in-situ self-reduction method to bind Pt nanoparticles in a porous silicon nanoparticle (PSi) skeleton for growth. Due to the presence of abundant Si-Hx bonds, the porous silicon nanoparticle PSi material has high reduction ability and can be used as a template and reducing agent for depositing small-sized metal NPs such as Ag, Pd and Cu. During the reaction, the Pt precursor obtains electrons from the surface hydride of the porous silicon nanoparticle PSi (Si-Hx) and is reduced to a metal Pt substance. Adding citric acid during the reaction can increase the acidity of the precursor solution and inhibit the hydrolysis of the noble metal salt. At the same time, the carboxyl functional group on the surface of the citric acid can effectively adsorb metal cations, thereby ensuring the uniform nucleation of the platinum precursor on the surface of the porous silicon nanoparticle PSi template during the in-situ reduction process.

[0055] In a specific embodiment provided by the present invention, the above steps are specifically: mixing porous silicon nanoparticles with water, then adding citric acid aqueous solution, heating, and then adding platinum precursor solution to react to obtain a silicon-based composite material.

[0056] In the present invention, the ratio of the porous silicon nanoparticles to water is preferably 1 g: (1-5) mL, more preferably 1 g: (1-4) mL, further preferably 1 g: (1-3) mL, and most preferably 1 g: 2 mL.

[0057] In the present invention, the concentration of the citric acid aqueous solution is preferably 1-2000 mg / mL, more preferably 5-200 mg / mL, further preferably 5-100 mg / mL, further preferably 10-50 mg / mL, further preferably 10-30 mg / mL, and most preferably 20 mg / mL.

[0058] In the present invention, the amount of citric acid aqueous solution added is preferably such that the pH value of the system is 4-7.

[0059] In the present invention, the heating temperature is preferably 50°C to 70°C, more preferably 55°C to 65°C, and most preferably 60°C.

[0060] In the present invention, the concentration of the platinum precursor solution is preferably 1-200 mmol / L, more preferably 5-200 mmol / L, more preferably 10-150 mmol / L, more preferably 10-100 mmol / L, more preferably 30-80 mmol / L, more preferably 40-60 mmol / L, and most preferably 50 mmol / L.

[0061] In the present invention, the reaction time after adding the platinum precursor solution is preferably 1 to 3 hours, more preferably 1.5 to 2.5 hours, and even more preferably 2 hours.

[0062] In the present invention, after the reaction, the solid is preferably collected and then washed with deionized water to remove excess reactants to obtain a silicon-based composite material.

[0063] The preparation method provided by the present invention can not only realize the rapid and mild aqueous phase modification of porous silicon nanoparticles (PSi), but also introduce precious metals, which has potential applications in the biomedical field and even in the catalytic field. In addition, the material can be further applied through subsequent surface modification. For example, due to the pore structure of PSi, drugs can be further loaded to achieve combined therapy.

[0064] The present invention also provides a silicon-based composite material with angiogenic and antibacterial activity prepared by the above preparation method, comprising porous silicon nanoparticles and nanoplatinum particles loaded on the porous silicon nanoparticles; the porous silicon nanoparticles have vertical channels.

[0065] In the present invention, the silicon-based composite material with angiogenic and antibacterial activity has excellent near-infrared absorption and photothermal conversion capabilities.

[0066] In the present invention, the silicon-based composite material having angiogenic and antibacterial activities has nanozyme catalytic activity.

[0067] The present invention also provides an application of the silicon-based composite material with angiogenic and antibacterial activities prepared by the above preparation method in the preparation of antibacterial materials.

[0068] Specifically, the antibacterial material is a photothermal-photodynamic synergistic antibacterial material. Due to Pt doping, the silicon-based composite material (Pt-PSi nanocomposite material) has better near-infrared photothermal conversion activity and higher peroxidase-like catalytic activity, achieving efficient antibacterial.

[0069] The present invention also provides an application of a silicon-based composite material with angiogenic and antibacterial activity prepared by the above-mentioned preparation method in the preparation of angiogenic materials. Endogenous ROS stimulation and exogenous NIR light stimulation can also drive the release of silicon ions in the silicon-based composite material to achieve efficient angiogenic treatment. This porous silicon-based composite material with angiogenic and antibacterial activity is not limited to the treatment of infected wounds. Such biofunctional materials may be applied to various tissues such as teeth, bones, etc.

[0070] The present invention also provides an application of the silicon-based composite material with angiogenic and antibacterial activity prepared by the above preparation method in the preparation of wound dressings.

[0071] The silicon-based composite material prepared by the present invention can be used for combined treatment of wounds, giving full play to the biocompatibility, vasoactive activity (PSi), photothermal and antibacterial activity (Pt) of the composite material. Therefore, the silicon-based composite material can achieve antibiotic-free treatment of bacterially infected burn wounds without loading drugs.

[0072] The present invention also provides a use of the silicon-based composite material with angiogenic and antibacterial activity prepared by the above preparation method as a catalytic electrode of a micro proton exchange membrane fuel cell.

[0073] In order to further illustrate the present invention, a silicon-based composite material with angiogenic and antibacterial activities, a preparation method thereof and applications thereof provided by the present invention are described in detail below in conjunction with examples.

[0074] The reagents used in the following examples are all commercially available.

[0075] Example 1

[0076] Preparation of PSi nanoparticles

[0077] Nano-PSi particles were prepared by electrochemical etching: a P-type boron-doped silicon wafer was fixed in an electrolytic cell, anhydrous ethanol and 40% hydrofluoric acid were added as electrolyte in a volume ratio of 1:4, the silicon wafer was used as anode, the platinum electrode was used as cathode, and the current density was 77 mA cm -1 The porous silicon layer was obtained by constant current electrolysis for 10 min. Then, the porous silicon was used as the anode and the platinum electrode was used as the cathode. The mass concentration of hydrofluoric acid in the etching solution was changed to 3.3% and the etching current density was 30 mA cm -1 , constant current etching was performed, and after 5 minutes, the exfoliated porous silicon film (PSi film) was obtained. Finally, the exfoliated PSi film was ultrasonically treated in ethanol (500W, 3h), the supernatant was centrifuged at 10000rpm for 10min, washed three times with ethanol to remove ultra-small particles, and the bottom product was collected to obtain PSi nanoparticles.

[0078] Preparation of Pt-PSi Silicon-based Composite Materials

[0079] To prepare the Pt-PSi nanocomposite, 1 g of the PSi nanoparticles prepared above was added to 2 mL of aqueous solution. Next, 100 μL of 20 mg / mL citric acid solution was added to the solution containing PSi and stirred thoroughly, and the pH of the system was adjusted to 4.0 with 0.01 M hydrochloric acid. Then, the mixed solution was heated to 60 ° C in a water bath. Next, 20 μL of chloroplatinic acid H2PtCl6 (50 mM) was quickly added to the above mixture, and the reaction lasted for 2 hours. Then, the dark black Pt-PSi nanocomposite was collected and washed 3 times with deionized water to remove excess reactants. Finally, the Pt-PSi product at the bottom was collected and stored at 4 ° C for further use.

[0080] Comparative experiment: explore the different pH values ​​without citric acid, after adding citric acid, and at the same pH, replace other complexing agents such as tartaric acid and trisodium citrate for comparison. Other reaction conditions remain the same.

[0081] Comparative Example 1

[0082] The preparation of PSi nanoparticles is the same as in Example 1.

[0083] 1 g of the prepared PSi nanoparticles was added to 2 mL of aqueous solution, and the pH of the system was adjusted to 4.0 with 0.01 M hydrochloric acid. Then, the mixed solution was heated to 60 ° C in a water bath. Next, 20 μL of chloroplatinic acid H2PtCl6 (50 mM) was quickly added to the mixture, and the reaction lasted for 2 hours. Then, the dark black Pt-PSi nanocomposite was collected and washed 3 times with deionized water to remove excess reactants. Finally, the Pt-PSi product at the bottom was collected and stored at 4 ° C for further use.

[0084] Comparative Example 2

[0085] The preparation of PSi nanoparticles is the same as in Example 1.

[0086] Next, add 100 μL of 20 mg / mL citric acid solution and stir thoroughly, and adjust the pH of the system to 3.0 with 0.01 M hydrochloric acid. Then, heat the mixed solution to 60 ° C in a water bath. Next, 20 μL of chloroplatinic acid H2PtCl6 (50 mM) was quickly added to the mixture and the reaction lasted for 2 hours. Then, collect the dark black Pt-PSi nanocomposite and wash it 3 times with deionized water to remove excess reactants. Finally, collect the Pt-PSi product at the bottom and store it at 4 ° C for further use.

[0087] Comparative Example 3

[0088] The preparation of PSi nanoparticles is the same as in Example 1.

[0089] Next, add 100 μL of 20 mg / mL citric acid solution and stir thoroughly, and adjust the pH of the system to 8.0 with 0.01 M NaOH. Then, heat the mixed solution to 60 ° C in a water bath. Next, 20 μL of chloroplatinic acid H2PtCl6 (50 mM) was quickly added to the mixture and the reaction lasted for 2 hours. Then, collect the dark black Pt-PSi nanocomposite and wash it 3 times with deionized water to remove excess reactants. Finally, collect the Pt-PSi product at the bottom and store it at 4 ° C for further use.

[0090] Comparative Example 4

[0091] The preparation of PSi nanoparticles is the same as in Example 1.

[0092] Next, add 100 μL of 20 mg / mL tartaric acid solution and stir thoroughly, and adjust the pH to 4.0 with 0.01 M hydrochloric acid system. Then, heat the mixed solution to 60 ° C in a water bath. Next, 20 μL of chloroplatinic acid H2PtCl6 (50 mM) was quickly added to the mixture and the reaction lasted for 2 hours. Then, collect the dark black Pt-PSi nanocomposite and wash it 3 times with deionized water to remove excess reactants. Finally, collect the Pt-PSi product at the bottom and store it at 4 ° C for further use.

[0093] Comparative Example 5

[0094] The preparation of PSi nanoparticles is the same as in Example 1.

[0095] Next, add 100 μL of 20 mg / mL trisodium citrate solution and stir thoroughly, and adjust the pH to 4.0 with 0.01 M hydrochloric acid system. Then, heat the mixed solution to 60 ° C in a water bath. Next, 20 μL of chloroplatinic acid H2PtCl6 (50 mM) was quickly added to the above mixture, and the reaction lasted for 2 hours. Then, collect the dark black Pt-PSi nanocomposite and wash it 3 times with deionized water to remove excess reactants. Finally, collect the Pt-PSi product at the bottom and store it at 4 ° C for further use.

[0096] Microstructure Analysis:

[0097] The PSi nanoparticles obtained in Example 1 were analyzed using a transmission electron microscope, and the transmission electron microscope image thereof was as follows: Figure 1 As shown, a is a PSi nanoparticle prepared by electrochemical etching, and b is a TEM image of the magnified pore area of ​​the PSi nanoparticle. Figure 1It can be seen that the PSi nanomaterial prepared in Example 1 is a PSi nanoparticle with a particle size of about several hundred nanometers, and at the same time shows abundant vertical channels, which can support the confinement and loading of drugs and small-sized metal nanoparticles.

[0098] The Pt-PSi silicon-based composite materials obtained in Example 1 and Comparative Examples 1 to 5 were analyzed using a transmission electron microscope, and the transmission electron microscope images thereof were as follows: Figure 2 As shown, a is the Pt-PSi silicon-based composite material obtained in Comparative Example 1, b is the Pt-PSi silicon-based composite material obtained in Example 1, c is the Pt-PSi silicon-based composite material obtained in Comparative Example 2, d is the Pt-PSi silicon-based composite material obtained in Comparative Example 3, e is the Pt-PSi silicon-based composite material obtained in Comparative Example 4, and f is the Pt-PSi silicon-based composite material obtained in Comparative Example 4. Figure 2 It can be seen that in the Pt-PSi silicon-based composite material obtained in Example 1, small-sized black Pt spherical nanoparticles can be clearly observed on the PSi material, and the distribution is uniform and dense. However, the comparative sample without adding citric acid or other pH or other complexing agent types obviously does not have small-sized uniform Pt nanomaterials, but generates some clustered aggregates or agglomerates wrapped on the PSi carrier. It shows that citric acid has an unexpected effect in adjusting the pH range and promoting uniform modification.

[0099] Study on photothermal characteristics:

[0100] The photothermal performance of the composite material was tested on a 48-well plate, using a vertical 808nm near-infrared (NIR) laser to irradiate at a distance of 10cm with a spot diameter of 1cm. In order to compare the photothermal conversion capabilities of different materials, an aqueous solution containing 500μL of the Psi nanoparticles obtained in Example 1 and the Pt-PSi silicon-based composite material (200μg / mL) obtained in Example 1 was irradiated with an 808nm near-infrared laser. A commercial thermal imager (FLIRSystem) was used to obtain thermal images at specific time intervals and record temperature changes to obtain 1W / cm at 808nm. 2 The photothermal curves of water, PSi material, and Pt-PSi composite material under NIR light irradiation are shown in the figure below. Figure 3 In addition, the photothermal stability of the Pt-Psi silicon-based composite material obtained in Example 1 was tested by three laser switching cycle experiments, and the photothermal curve of the Pt-Psi silicon-based composite material after three cycles of laser irradiation was obtained as shown in FIG. Figure 3 As shown in b. Figure 3 It can be seen from Figure a that under near-infrared laser irradiation, the temperature of the aqueous solution containing the Pt-PSi material obtained in Example 1 rises rapidly. After 10 minutes of irradiation, the platform temperature of the Pt-PSi group can reach 50.3°C, which is about 20°C higher than that of PSi. In addition, Figure 3 The three-cycle test in b shows that the photothermal performance of Pt-PSi material is stable and can be used multiple times with almost no change. The above experimental results show that Pt-PSi nanocomposites have good near-infrared photothermal conversion performance.

[0101] Catalytic effect of nanozymes:

[0102] In order to investigate the nanozyme catalytic performance of the composite material, the classic H2O2-trimethylbenzidine (TMB) color reaction was used. Its main reaction mechanism is to use peroxidase-like enzymes to catalyze the decomposition of H2O2 substrates to generate hydroxyl radicals (·OH), which can effectively catalyze the oxidation and discoloration of TMB. The oxidized TMB has a maximum absorption peak at 650nm and can be used as an indicator to study the catalytic activity of Pt-PSi nanozymes.

[0103] The steps for studying the catalytic effect of nanozymes are as follows: 100 μL of PSi (prepared in Example 1) or the Pt-PSi silicon-based composite material (2 mg / mL) prepared in Example 1 was added to 900 μL of PBS solution (50 mM, pH = 6.5) containing H2O2 (10 mM) and TMB (3,3',5,5'-tetramethylbenzidine, 0.5 mM), and one of the PBS solutions containing the Pt-PSi silicon-based composite material prepared in Example 1, H2O2 and TMB was heated at 808 nm 1 W / cm 2 The system was irradiated with NIR light, and the rest of the system was under visible light conditions. Then, after reacting at room temperature for 10 minutes, the absorbance was measured using a UV spectrometer. At the same time, the change in the absorbance value at 652nm within 10min was recorded, and the nanozyme activity test results of the material were obtained as follows Figure 4 As shown. Figure 4 It can be seen that peroxidase nanozymes can catalyze the oxidation of the chromogenic substrate TMB to produce an absorption peak at 650nm. Due to the lack of enzyme or low catalytic activity of PSi, the absorbance value of the reaction system did not change significantly in the blank group and the PSi group. On the contrary, the absorption of the Pt-PSi group changed significantly, and a characteristic absorption peak of oxidized TMB appeared at 650nm, indicating that the catalytic reaction had occurred. In addition, it was found that under 808nm near-infrared laser irradiation, the catalytic performance of the reaction system was further improved. The reason for the above phenomenon may be due to the excitation of thermal electrons on the surface of Pt metal under near-infrared light irradiation, resulting in enhanced electron transfer and catalytic ability. On the other hand, the increase in the temperature of the reaction system caused by the photothermal effect will also accelerate the kinetics of the catalytic reaction.

[0104] Silicon ion release study:

[0105] The effective bioactive Si ion release from PSi degradation activity will be beneficial for pro-angiogenic therapy. Since Pt-PSi nanocomposites have excellent photothermal activity and peroxidase-like activity, it is reasonable to speculate that these two properties will endow the smart nanocomposites with stimuli-responsive ion release behavior.

[0106] In order to test the ion release behavior, 500 μg / mL of the Pt-PSi silicon-based composite material obtained in Example 1 was incubated in a phosphate buffer solution (PBS, pH=6.5) at 37°C, and the supernatant was collected at different time points. In addition, the release of silicon ions in the presence of highly reactive oxygen (1 mM H2O2) and near-infrared laser treatment (1 W / cm 2 The release of inorganic silicon ions in the supernatant was measured by inductively coupled plasma optical emission spectrometry (ICP-OES, Varian 715-ES), and the cumulative release percentage was calculated. Each test group contained three parallel samples, and the release of silicon ions from the material degradation dissolution in a buffer solution simulating the wound microenvironment was investigated as shown in the figure. Figure 5 As shown. Figure 5 It can be seen that both H2O2 and near-infrared light stimulation significantly accelerated the degradation of PSi, thereby accelerating the release of silicon ions. The combination of these two factors further enhanced the promotion effect. The reason for the above phenomenon is that PSi is an oxidation-induced degradation material, and the degradation of PSi is also thermosensitive. Therefore, the present invention proposes a new PSi-based treatment strategy, in which the reactive oxygen species generated by H2O2 catalyzed by nanozymes and the heat generated by near-infrared laser irradiation can be used as a dual stimulus to drive PSi degradation and on-demand ion release, which has good application prospects in promoting angiogenesis to treat wounds.

[0107] In vitro antibacterial test:

[0108] Under the stimulation of the excellent photothermal and enzyme-like activities of Pt-PSi nanocomposites, the present invention then used Staphylococcus aureus as a test model and treated Staphylococcus aureus with different materials in the culture medium. Then, the plate count method was used to determine the number of viable bacteria in each group after treatment, and its in vitro antibacterial effect was studied, and the corresponding antibacterial rate was calculated.

[0109] Staphylococcus aureus was used as a bacterial model to evaluate its antibacterial ability. First, the bacteria were grown in a liquid culture medium on a constant temperature oscillator (37°C) overnight. Subsequently, the PSi obtained in Example 1 and the Pt-PSi obtained in Example 1 were added to 5×10 6CFU / mL bacterial suspension. To simulate the wound environment, the solution also contained 1 mM H2O2. In particular, the Pt-PSi+NIR group was illuminated by a near-infrared laser (1.0 W / cm 2 ) for 10 minutes. Then, 10 μL of the treated culture medium was collected and cultured in a 96-well plate for different time periods. The absorbance value of each group of bacteria was measured by a microplate reader. At the same time, 10 μL of the bacterial suspension was diluted 10 4 After 12 hours of incubation at 37°C, the colonies were photographed and quantitatively analyzed using ImageJ software to obtain a comparison of the antibacterial effects of different groups. Figure 6 As shown in the figure, a is the colony map and b is the quantitative analysis result. Figure 6 It can be seen that due to the lack of photothermal and catalytic activity, PSi nanoparticles have almost no inhibitory effect on bacterial growth regardless of near-infrared laser irradiation. However, Pt-PSi nanocomposites have good bactericidal effects and can almost completely inhibit bacterial growth after near-infrared laser irradiation. Synergistic treatment based on Pt-PSi nanocomposites can significantly improve the bactericidal effect and reduce bacterial survival rate. Under the action of 808nm near-infrared laser, the bacterial survival rate after Pt-PSi treatment is only 4.8%, which is much lower than the bacterial survival rate of single nanozyme catalytic treatment (63.7%).

[0110] In vitro cytocompatibility test:

[0111] The in vitro cytotoxicity of Pt-PSi nanocomposites on endothelial cells HUVECs was studied using CellTiter-Lumi reagent.

[0112] Specifically, human umbilical vein endothelial cells (HUVECs, Sciencell) were cultured in a 37°C / 5% CO2 humidified incubator for further use. To evaluate cell compatibility, HUVECs were cultured in a 96-well plate for 24 hours, and then different concentrations of the Pt-PSi silicon-based composite material obtained in Example 1 were added to the culture medium (endothelial cell growth DMEM culture medium). The control group was irradiated with 808nm laser for 10min (1.0W / cm 2 After that, the cells were cultured for another 48 hours, and the culture medium was replaced with 150 μL CellTiter-Lumi (Beyotime) reagent. The luminescence intensity of the cells co-incubated with the material was measured using a multifunctional microplate reader (Tecan, Inlimited M200Pro). The relative cell viability was calculated by comparing with the control group, and the corresponding cell viability detection results of the Pt-PSi material under NIR laser irradiation and without NIR laser irradiation were obtained as shown in the figure. Figure 7 As shown. Figure 7It can be seen that when 500 μg / mL of Pt-PSi nanocomposite was used alone, the cell viability remained at 92.4%, indicating low cytotoxicity. Further near-infrared laser treatment of Pt-PSi nanocomposite could not significantly reduce HUVEC cell viability. The good cytocompatibility of Pt-PSi nanocomposite may be due to the fact that the loading of metal nanomaterials in PSi can reduce the probability of contact with cells, thereby reducing its cytotoxicity.

[0113] Cell migration ability test:

[0114] The effects of different treatments on cell migration were studied by standard scratch test. Specifically, in order to test the migration behavior of cells, HUVEC (5×10 cells per well) were firstly cultured in 4 ) were inoculated and grown overnight to form a monolayer on a 6-well plate. Then, a pipette tip was used to create a direct scratch on the HUVEC monolayer. Subsequently, the cells were washed three times with PBS (0.01 M). Fresh cell culture medium (endothelial cell growth DMEM medium) containing PSi (200 μg / mL) or Pt-PSi (200 μg / mL) obtained in Example 1 was then added. For the NIR group, 808 nm laser (1.0 W / cm 2 ) irradiated the cells for 10 min. After 12 hours of culture, the scratches were observed under an optical microscope to obtain the effects of different treatment groups on the migration ability of endothelial cells. Figure 8 As shown. Figure 8 It can be seen that the scratch area in the PSi group increased slightly compared with the control group. However, after treatment with Pt-PSi and Pt-PSi+NIR materials at a concentration of 500μg / mL, the scratch area was further reduced due to the rapid release of silicon ions. After 12h, the Pt-PSi+NIR group dropped significantly to 22.7%, which was significantly smaller than the no-NIR group (35.9%). These results show that near-infrared laser and nanozyme-mediated degradation strategies can effectively enhance the ability to promote cell migration.

[0115] In vivo angiogenesis assay:

[0116] In order to further study the effect of the material on angiogenesis in vivo, the present invention conducted an in vivo CAM experiment in a chicken embryo model.

[0117] The in vivo angiogenesis of the complex was tested by an in vivo chick embryo angiogenesis assay. First, fertilized eggs were incubated in an incubator at 38°C and 60% humidity for 7 days. Then, a PBS solution containing Psi or Pt-PSi obtained in Example 1 (200 μg / mL) was carefully injected into the chorioallantoic membrane (CAM) of 7-day-old chick embryos using a syringe. The angiogenesis was tested by an 808 nm laser (1 W / cm 2) irradiated Pt-PSi+NIR group for 10 min. Then the eggs continued to incubate at 38°C for 1 day. On the 8th day, the top window was opened and photos were taken with a digital camera to obtain the in vivo vascular experiment photos as shown in the figure. Fig. 9 As shown. Fig. 9 It can be seen that the angiogenesis levels of PSi, Pt-PSi, and Pt-PSi+NIR groups were significantly improved compared with the Ctrl group. The Pt-PSi+NIR group had the most obvious branched vessels, indicating a higher degree of vascular maturity.

[0118] In vivo wound healing experiment:

[0119] The present invention establishes a skin burn infection model to evaluate the comprehensive wound healing properties of nanomaterials in vivo.

[0120] Twenty BALB / c mice (6 weeks) were randomly divided into a control group (PBS), a PSi group, a Pt-PSi group (obtained in Example 1), and a Pt-PSi (obtained in Example 1) + NIR group. A flat-headed metal rod was electrically heated to 100°C and contacted with the back skin of the rat for 30 seconds to establish a burn wound model. The wound was then trimmed with surgical scissors. Then, a solution containing 10 7 The wound surface was infected with a suspension of 1000 CFU / mL Staphylococcus aureus for one day to establish a burn infection wound model that is difficult to heal. During the healing process, PBS solutions (500 μg / mL, 250 μL) containing different materials were sprayed on the wound surface every two days. The laser treatment group was treated with near-infrared light (1 W / cm 2 The wound healing process was observed two weeks later, and the wound images were recorded. The wound healing rate was analyzed using ImageJ software. The images of the wound sizes at different time points after treatment in different groups and the quantitative analysis results of the wound size were obtained as shown in the figure. Fig.10 As shown. Fig.10 It can be seen that wound photos during the healing process were recorded on the 1st, 5th, 9th and 13th days, and the changes in wound size were analyzed by ImageJ software. Since the control group was not treated, the wound area remained above 40% of the original area after 13 days, indicating the difficult-to-heal characteristics of burn infection wounds. In addition, there was no significant improvement in wound healing after PSi treatment. In contrast, the Pt-PSi and Pt-PSi+NIR groups were better than the other groups in promoting wound healing. In particular, at multiple time points, the wound size of the Pt-PSi+NIR group after treatment was significantly smaller than that of the other groups, and the wound was almost completely healed on the 13th day. These results show that the Pt-PSi nanocomposite prepared by the present invention has good properties of accelerating wound healing in vivo.

[0121] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a silicon-based composite material having angiogenic and antibacterial activities, characterized in that: The following steps are involved: S1) providing porous silicon nanoparticles; S2) The porous silicon nanoparticles and citric acid are mixed and heated in water, and then a platinum precursor is added to react to obtain a silicon-based composite material.

2. The preparation method according to claim 1, characterized in that: In the step S2), the pH value of the system is adjusted to 4-7 after mixing.

3. The preparation method according to claim 1, characterized in that: The platinum precursor is selected from one or more of chloroplatinic acid, platinum chloride and platinum acetate.

4. The preparation method according to claim 1, characterized in that: The reaction temperature in step S2) is 50°C to 70°C; the reaction time is 1 to 3 hours.

5. The preparation method according to claim 1, characterized in that: The step S2) is specifically as follows: The porous silicon nanoparticles are mixed with water, and then a citric acid aqueous solution is added, heated, and then a platinum precursor solution is added to react to obtain a silicon-based composite material.

6. The preparation method according to claim 5, characterized in that: The concentration of the citric acid aqueous solution is 1 to 2000 mg / mL; The concentration of the platinum precursor solution is 1 to 200 mmol / L; The ratio of the porous silicon nanoparticles to water is 1 g: (1-5) mL.

7. The preparation method according to claim 5, characterized in that: The porous silicon nanoparticles are prepared according to the following method: A1) using a P-type boron-doped silicon wafer as an anode and a mixed solution of ethanol and a 40-50 wt % hydrofluoric acid aqueous solution as an electrolyte, performing constant current electrolysis to obtain a porous silicon layer; A2) using the porous silicon layer as an anode and a 3-5 wt % hydrofluoric acid aqueous solution as an etching electrolyte to perform constant current etching to obtain a porous silicon film; A3) The porous silicon film is subjected to ultrasonic treatment to obtain porous silicon nanoparticles.

8. The silicon-based composite material with angiogenic and antibacterial activity prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The invention comprises porous silicon nanoparticles and nano-platinum particles loaded on the porous silicon nanoparticles; the porous silicon nanoparticles have vertical channels.

9. Use of the silicon-based composite material having angiogenic and antibacterial activities prepared by the preparation method according to any one of claims 1 to 7 in the preparation of angiogenic materials.

10. Use of the silicon-based composite material with angiogenic and antibacterial activity prepared by the preparation method according to any one of claims 1 to 7 in the preparation of wound dressings.

Citation Information

Patent Citations

  • Biodegradable porous silicon particles and application thereof in promoting vascularization

    CN112142054A

  • Preparation method and application of ferroferric oxide composite nano-enzyme antibacterial agent

    CN114053473A

  • Copper-based nano-enzyme active material for repairing multiple wound surfaces difficult to heal, application of copper-based nano-enzyme active material and wound repairing gel

    CN115501339A

  • Nano-enzyme with dual functions of resisting bacteria and removing excessive reactive oxygen species and preparation method of nano-enzyme

    CN116019928A

  • Preparation method of multifunctional nanofiber membrane for promoting healing of complex infected wound

    CN118286487A